Social determinants of sexual and reproductive health : informing future research and programme implementation - Malarcher, Shawn (WHO GenevaCH, 2010)
Examines the relationship between the organisation of the health system and sexual and reproduction health and, the relationship between social conditions of vulnerability, (e.g. poverty, migration,and social exclusion), institutions (e.g. schools), behaviours (e.g. sexual violence or coercion) and sexual and reproductive health. Contributes to a growing consensus advocating for the inclusion of equity as a key concept in measuring programme success.